Snow Sports Trauma and Safety 2017
DOI: 10.1007/978-3-319-52755-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Skiing and Snowboarding in Switzerland: Trends in Injury and Fatality Rates Over Time

Abstract: Introduction: Skiing and snowboarding are two of the most popular sports in Switzerland, but their popularity means that the absolute number of injuries remains high. To plan and evaluate effective injury prevention, detailed insights into the injuries that occur are needed. Objective: The aim of this study was to characterize the current status (average winter season 2008-2012) and trends in injury rate (between 2005 and 2012) and fatality rate (between 2000 and 2014) among skiers and snowboarders in Switzerl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…In comparison, studies by Shealy et al [9] and Ruedl et al [6] reported 38.5 ± 6.0 and 41.1 ± 6.4 deaths on average per winter season. The overall incidence rate of 0.70 deaths per million skier days is lower than shown in studies by Ruedl et al [6], Shealy et al [9] and Bianchi et al [8], reporting 0.79, 0.75 and 0.70 deaths per million skier days.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…In comparison, studies by Shealy et al [9] and Ruedl et al [6] reported 38.5 ± 6.0 and 41.1 ± 6.4 deaths on average per winter season. The overall incidence rate of 0.70 deaths per million skier days is lower than shown in studies by Ruedl et al [6], Shealy et al [9] and Bianchi et al [8], reporting 0.79, 0.75 and 0.70 deaths per million skier days.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, the present study included all deaths, both traumatic and nontraumatic, while Shealy et al [9] and Bianchi et al [8] only documented traumatic deaths. In the underlying study, the incidence of traumatic deaths was 0.36 per million skier days and was much lower compared to incidences reported by studies of Shealy et al [9] and Bianchi et al [8]. The abovementioned studies [8,9] analyzed deaths rates in the period from 1991/92 to 2012.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of sustaining an injury while snowboarding is higher than alpine skiing [2][3][4] and injury rates are among the highest of all sports in the 9 to 19-yearold age group [5]. In snowboarding, the wrist is the most frequently injured region [6][7][8], with wrist fractures a common occurrence [9].…”
Section: Introductionmentioning
confidence: 99%